System of Environmental-Economic Accounting 2012 : Experimental Ecosystem Accounting - United Nations (New York: United Nations, 2016)
Ecosystem accounting is a coherent and integrated approach to the assessment of the environment through the measurement of ecosystems, and measurement of the flows of services from ecosystems into economic and other human activity. The scale on which the accounting may be conducted varies: the ecosystems measured may range from specific land cover type areas, such as forests, to larger integrated areas, such as river basins, and may include areas considered to be relatively natural and those that are heavily affected by human activity, such as agricultural areas. The System of Environmental-Economic Accounting 2012—Experimental Ecosystem Accounting (SEEA Experimental Ecosystem Accounting) constitutes an integrated statistical framework for organizing biophysical data, measuring ecosystem services, tracking changes in ecosystem assets and linking this information to economic and other human activity.